Social Network of Urban and Rural Elderly with Disability in Indonesia - Widagdo, The Maria Meiwati; Putri, Gusti Ayu Agung Indra Sari; Widyaningsih, Bernadeta Dhaniswara (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study aimed to compare the social network between rural and urban elderly with disability. Methodology: The study participants were community dwelling rural and urban elderly with disability. Disability was assessed using Washington Group Short Set of questions on functioning and social network was rated using the Lubben Social Network Scale. Data were analysed using ANOVA test and crosstabulation to gain a deeper understanding with demographic variables. Results: A total of 115 (55 rural and 60 urban) elderly with disability aged 60-95 years participated in this study. Rural elderly with disability are more involved in social networking. Urban elderly women seem to experience higher rates of isolation. Rural men exhibit higher level of social networking compared to urban men and women in both rural and urban settings. Elderly who have education have higher social network than those without education. Married elderly, particularly in rural areas, have higher levels of social networking and lower rates of isolation compared to those who are single. Single elderly, especially in urban areas, are more vulnerable to social isolation. Applications/Originality/Value: Rural older people with disability have higher social networking than their urban counterparts. The findings that sociodemographic and geographic factors shape social network of elderly with disability emphasize the needs of social policies and community-based programs targeting urban elderly with disability, particularly women, those who are single or have lower education.